2016
DOI: 10.1111/ctr.12745
|View full text |Cite
|
Sign up to set email alerts
|

Skype clinics after intestinal transplantation – follow‐up beyond post codes

Abstract: The follow-up after intestinal transplantation (ITX) is complex and limited to specialized centers. ITX recipients often travel all over the country to be seen in the outpatient clinic of specialized centers which is costly and time-consuming. Videoconferences through Skype have been implemented to eliminate travel time, costs, and to improve patient compliance without jeopardizing safety. Eighteen of 19 patients followed up after ITX or modified multivisceral transplantation (MMVTX) in conventional outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…This is similar to other studies in both solid organ transplant and nontransplant settings where patients rated telehealth visits highly in terms of satisfaction 2. A small study out of the UK examined outcomes in intestinal transplant recipients followed by Skype 11. After a median of 180 days post-transplant, patients were given a choice between continued monthly clinic visits or weekly Skype conferences plus in-person visits every 3 months.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This is similar to other studies in both solid organ transplant and nontransplant settings where patients rated telehealth visits highly in terms of satisfaction 2. A small study out of the UK examined outcomes in intestinal transplant recipients followed by Skype 11. After a median of 180 days post-transplant, patients were given a choice between continued monthly clinic visits or weekly Skype conferences plus in-person visits every 3 months.…”
supporting
confidence: 69%
“…and survival in this group. A small study out of the UK examined outcomes in intestinal transplant recipients followed by Skype 11. This is a patient population selected for having survived to the inception of our telehealth program, which may have been many years post-transplant, as opposed to survival in all comers from the time of transplant.…”
mentioning
confidence: 99%
“…exploring issues of usability and acceptability). 45,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Many focus specifically on the clinical use of Skype, 91,[114][115][116][117][118][119][120][121][122][123] either on its own or in combination with other technologies [e.g. WhatsApp (WhatsApp Inc., Mountain View, CA, USA) messaging 124 or FaceTime 125,126 ].…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
“…Across these studies, despite reported benefits (e.g. in terms of increased access for patients [9,[28][29][30] particularly those with complex needs, [31] patient and clinician satisfaction with the remote option, [23,[32][33][34][35] potential time/cost savings, [8,36,37] improvement in self-management skills, [38] and improved compliance to treatment and/or clinical outcomes [17,22,24,31,[39][40][41][42][43]) small sample sizes (e.g. five patients) and high losses to follow-up prevent any unqualified conclusion that remote consultations are 'effective'.…”
Section: Introduction Backgroundmentioning
confidence: 99%